Competitiveness factors in the innovative enterprises in the North-East voivodeships in Poland - Kamil Decyk (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
The research problem was the connection about the problematics of competitiveness factors with the planned action of innovation within the managing of the enterprise. In such research area the purpose of the study was to identify and evaluate the competitiveness factors used in innovative companies while taking into consideration companies' ownership of long-term plan of action connected with managing the innovations. To achieve this objective, the following research methods were used: analysis of national and foreign literature resources, survey measurement (observation technique), direct and indirect interview, research tool: questionnaire. The results were analysed with statistical methods such as arithmetic mean, test of Kruskal-Wallis, Chi-square test (χ2), and measure of association including Cramér's V coefficient were applied. Based on research results and mentioned statistical tools, it was stated that having of long-term plan of action connected with innovations statistical significant affected on the evaluated competitiveness factors (innovativeness, quality, marketing and logistics activities) except the price. It was confirmed in such wat the first research hypothesis. The research also showed a relationship between competing using innovativeness and having an action plan related to innovations, however, this relationship was not statistically significant. As a result, the research hypothesis can be neither rejected nor confirmed. In practical terms, the conducted research points out the competitiveness factors which are suggested to use by the innovative enterprises in order to improve their competitiveness against competitiveness and in surroundings of knowledge based economy, as well the digital economy. Results of the research indicate at the same time, the necessity of development of long-term plan of action connected with innovations, which provides bigger possibilities in range of usage of competitiveness instruments on the market by enterprises.
Keywords: O31; O32; 650; competitiveness; competitiveness factors; innovativeness; innovative company; innovation management; long-term action plans; strategic management